2012
DOI: 10.1002/etc.1911
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessible heavy metals-sediment particles from Reconquista River induce lung inflammation in mice

Abstract: The Reconquista River (RR), one of the most polluted watercourses in Argentina, receives effluent discharges from heavily industrialized and highly populated settlements. During winter and summer, the floodplain remains dry, producing the oxidation of sulfide and organic matter present in the sediment, making heavy metals more bioaccessible. Dispersion of this sediment occurs, and thus harmful effects on the pulmonary health of residents and workers inhabiting the RR bank may take place. The authors characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…studied the presence of bioaccessible heavy metalssediment particles from Reconquista River (RR-PM), one of the most polluted watercourses in Argentina. 29 The River receives effluent discharges from heavily industrialized and highly populated settlements. To this end, authors studied how this pollution induces lung inflammation in mice evaluating the biological impact of this particles on the respiratory system of BALB/c mice.…”
Section: Edx Microanalysis In Heavy Metals Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…studied the presence of bioaccessible heavy metalssediment particles from Reconquista River (RR-PM), one of the most polluted watercourses in Argentina. 29 The River receives effluent discharges from heavily industrialized and highly populated settlements. To this end, authors studied how this pollution induces lung inflammation in mice evaluating the biological impact of this particles on the respiratory system of BALB/c mice.…”
Section: Edx Microanalysis In Heavy Metals Identificationmentioning
confidence: 99%
“…Moreover, they obtained that the sensibilized and exposed to particles groups had more dramatic adverse response. 29 …”
Section: Edx Microanalysis In Heavy Metals Identificationmentioning
confidence: 99%
“…DCC was determined after cell fixation with methanol and staining with hematoxylin-eosin. At least 200 cells in each sample were counted by light microscopy (Ferraro et al 2012).…”
Section: Total Cell Number (Tcn) and Differential Cell Count (Dcc)mentioning
confidence: 99%
“…In this context, we recently analyzed the composition and biological impact of the PM from RR sediment (RR-PMs) on lung mice (Ferraro et al 2012). We showed that RR-PMs composition includes particles of heterogeneous sizes (agglomerates PM10 and PM2.5) with the presence, in its bioaccesible phase, of metals traces such as lead (Pb), cadmium (Cd), chromium (Cr) and sulfur (S) and that the cytotoxic and proinflammatory effects found in the respiratory tract are mostly determined by its metal content.…”
mentioning
confidence: 99%
“…Many authors have studied their toxicological impacts on the biota (Herkovits et al, 1996;Loez & Topalia ´n, 1999;Ossana et al, 2013Ossana et al, , 2016Rigacci et al, 2013). Of note, heavy metals retained in sediment particles (Cantera et al, 2018;Tufo et al, 2021) may eventually be released to water and generate adverse effects in exposed animals and humans (e.g., Ferraro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%